Pendampingan Pasien Kanker Sistem Reproduksi Wanita Melalui Therapi Akupressure Sebagai Upaya Mengurangi Efek Kemotherapi Di Rumah Singgah Kanker Baiti Jannati Bengkulu - Metasari, Des; Rahmawati, Diyah Tepi; Sianipar, Berlian Kando; Diniarti, Fiya (Jurnal Dehasen Untuk Negeri, 2024)
Cancer of the reproductive system is the most common type of cancer suffered with the highest order of breast cancer after cervical cancer. Kemotherapi is one of the therapies undertaken by cancer patients including patients with reproductive system cancers including breast cancer and mammal cancer, this motherfire uses chemicals that can cause side effects in patients including headaches (myalgia), nausea and vomiting, alopecia etc. Acupressure is one type / way of health care that is done through pressing techniques on the surface of the body on acupuncture points using fingers, or other body parts, or blunt-tipped aids with health purposes. The acupressure method prioritizes promotive and preventive., Acupressure can also reduce pain in cancer patients as a result of motherhood, besides that it can also reduce nausea and vomiting. The purpose of this service is to find out that acupressure carried out on cervical cancer patients and breast cancer who undergo mothership can reduce side effects due to motherhood that is adopted. The method of this study was to acupressure patients who treated motherfire at the Biati Jannati halfway house as much as 15 pasein, The results of this study showed that there was a decrease in maternal side effects after acupressure for 1 month with decreased side effects in the form of pain, nausea and vomiting